KONSUMSI VITAMIN C DAN ZAT BESI PADA ANEMIA DEFISIENSI BESI - Afriandi, Dian; Aktalina, Lucia (Majalah Ilmiah METHODA, 2023)
The prevalence of iron deficiency anemia in Indonesia is around 57.1% and often occurs in adolescent girls. Iron deficiency anemia can result in impaired hemoglobin function, low productivity, hampered mental and intelligence development as well as a decrease in the body's immune system and morbidity. Macronutrients such as carbohydrates, proteins and fats are needed in hemoglobin biosynthesis. Likewise micronutrients such as iron, folic acid, vitamin C and vitamin B and micronutrients. This research aims: to determine the intake of vitamin C and iron and the incidence of anemia in students of the UISU Medan medical faculty. This type of research is observation using a cross-sectional design. The population was all students from the second semester of the UISU medical faculty, totaling 134 people. A sample of 50 people was taken randomly. This research showed that 58% of respondents did not consume insufficient amounts of vitamin C and 42% consumed sufficient amounts of vitamin C. The research results showed that 44% of respondents consumed sufficient iron and 56% did not consume enough iron. There were 18% of respondents who suffered from anemia. Conclusion: Based on the Chi square test, there is a significant relationship between iron intake and the incidence of anemia (p value <0.05) and there is no significant relationship between vitamin C consumption and the incidence of anemia (p value > 0.05).